Dengue: biology, diagnosis and pathology - Gubler, Duane J. (Henry Stewart Talks, 2020)
Basic biology and epidemiology of dengue viruses, Clinical and laboratory diagnosis, Risk factors for severe disease and epidemic transmission, Case studies of dengue epidemic